MGNREGA Program Asset Selection: A leaflet providing women information on how to participate - Kosec, Katrina; Kyle, Jordan; Narayanan, Sudha; Raghunathan, Kalyani (International Food Policy Research Institute, 2023)
The International Food Policy Research Institute (IFPRI), one of the research centers within the global Consultative Group on International Agricultural Research (CGIAR), has a long history of gender research relevant to its mission of reducing poverty and ending hunger and malnutrition. One of the concerns with women’s empowerment beyond the household – in public spaces, including community decision-making processes – is that women lack key pieces of information necessary to facilitate their full and effective participation. This document is a leaflet designed by IFPRI in collaboration with our partner, Academy of Management Studies (AMS), for women in Odisha, India who hold job cards under the Mahatma Gandhi National Rural Employment Guarantee Act (MGNREGA) program and thus have a right to influence the selection of the assets to be built by community members under the program. The purpose of the leaflet is to inform women about their rights to participate as well as some specifics on how and when to do so. It is used in conjunction with other interventions, including a public speaking training and a role model video, being deployed in Odisha in 2023 in order to expand women’s voice and agency in asset selection.